Fibrinogênio como fator de risco independente de doença vascular cerebral - Fukujima, Marcia Maiumi [UNIFESP] (1997)
We have studied fibrinogen levels (Clauss technique) in atherothrombotic ischemic stroke patients, in order to determine its role as a thombogenic risk factor. Twenty nine patients (20 men and 9 women) between 25 and 79 years old were studied; they all have had a atherothrombotic stroke. They were classified into two groups according to the result of their carotid doppler ultrasonography: g1 - without carotid flow reduction (n=l 9) and g2 - with carotid flow reduction (n=10). The fibrinogen mean value was 269mg/dl in gl and 353 mg/dl in g2. There were 47% of patients in gl and 80% of patients in g2 who presented levels >300 mg/dl. The proportions of the groups were significantly different (p<0,05). Considering the epidemiological value of 300 mg/dl, we conclude that the fibrinogen can be an independent risk factor for ischemic atherothrombotic stroke, specially in those whose carotid flow is reduced.